Pre-operative Anxiety Compounding Intra-operative Hypotension in Parturient women undergoing Cesarean Deliveries under Spinal Anesthesia - Saleem Pervaiz Bajwa, Shahida Sheraz, Aftab Hussain, Muhammad Akram, Umer Khan, Muhammad Asif Saleem (Journal of Rawalpindi Medical College, 2021)
OBJECTIVE: To assess the relation of intra-operative hypotension with severity of pre-operative anxiety in patients undergoing caesarean section under spinal anesthesia. STUDY DESIGN: Prospective observational study. PLACE AND DURATION OF STUDY: This study was carried out from June 2017 to May 2018 at anesthesia department of Combined Military Hospital Lahore. METHODOLOGY: One hundred and twenty patients belonging to America Society of Anesthesiology class I and II, undergoing caesarean section under spinal anesthesia were selected. Verbal Analogue Scale for anxiety (VASA) and Straight Trait Anxiety Inventory (STAIs) questionnaire were used to measure pre-operative anxiety. Patients were divided into three groups as mild (VASA<3or STAIs<44), moderate (VASA 4-7 or STAIs 44-55) and severe (VASA 7-10 or STAIs>55) anxiety. Baseline mean arterial pressure was measured. Patients were placed in supine position immediately after induction of spinal anesthesia at L3-L4 or L4-L5 level with 12mg bupivacaine. Blood pressure was measured every two minutes until the delivery of baby. Hypotension was labeled when mean arterial pressure dropped by 20% below the baseline. The effect of level of anxiety on drop in MAP was assessed. RESULTS: Seventeen (14.17%) patients had mild pre-operative anxiety; out of which four (23.53%) developed hypotension. Seventy three (60.83%) patients had moderate anxiety; out of which twenty seven (36.99%) developed hypotension. Thirty (25%) patients had severe anxiety; out of which twenty two (73.33 %) developed hypotension. P-value (0.001) was quite significant. CONCLUSION: It was concluded in our study that severity of pre-operative anxiety has significant effect on intra-operative spinal hypotension.